Teachers' experiences of school-based support in their work with shy students. (March 2022) - Solberg, Stine; Nyborg, Geir; Mjelve, Liv Heidi; Edwards, Anne; Arnesen, Anne
Abstract: We report on the support from senior leaders, outside agents and parents, experienced by Norwegian elementary school teachers while working with shy students. A national sample completed a questionnaire based on teacher interviews. A descriptive analysis examined experienced support; while a person-centered analysis revealed different profiles of teachers in relation to support. The findings show that teachers perceived some support in this work. But there were two profiles of teachers, one experienced significantly more support than the other. Class size was the only background variable that showed an effect on the profiles. Implications for schools and senior leadership are discussed.